INFLUENCE OF CALCIUM CONCENTRATION IN DRINKING WATER WITH CALCIUM URINE ON MALE AT RA’AS VILLAGE, KLAMPIS SUBDISTRICT, BANGKALAN REGENCY, MADURA - Fitriyah Amin Daman (Wiraraja Medika : Jurnal Kesehatan, 2012)
An elevated calcium concentration in drinking water can cause urinary tract stones. Calcium in such water is suspected to increase its level in urine. A high calcium level in urine is the risk factor of calcium stones occurrence. The aim of this research was to analyze the effect of calcium level in drinking water with calcium level in urine oin men at Ra’as village of Klampis, Bangkalan Region. This study used cross sectional design. It was located in Ra’as and Klampis Barat village. Samples are of 44 respondents consisted of 22 study groups and 22 comparison groups. This research would analyze the effect of calcium level in drinking water on calcium level in urine using multiple regression test. The result of comparison test showed that there was a significant difference in the food intake from calcium sources (p= 0.006), calcium level in drinking water (p= 0.000), calcium level in urine (p= 0.000) and calcium stones (p= 0.048) between study groups and comparison groups. Whereas, there was no significant difference for protein intake (p=1.000), salt intake (p= 0.896) and drinking water consumption (p= 0.799). Conclusion is there was an effect on calcium level in drinking water with calcium urine (p= 0.000).We recommended to using drinking water in addition to ground water to reduce the risk of hypercalciuria and cooking ground water before consumption.Keywords : Calcium concentration in drinking water, calcium urine, hypercalsiuria